Perfil de serviços farmacêuticos prestados em uma farmácia comunitária em Natal/RN - Marinho, Hugo Victor (2019)
The professional pharmacist is in a strategic establishment, in the pharmacy or drugstore, of wide reach to the population. Pharmaceutical care aims to achieve concrete results in response to prescribed therapy, improving the patient's quality of life. The pharmaceutical services provided in these establishments contribute to complement the medical service in health care, enabling a follow-up of the clinical condition, aiming at therapeutic effectiveness; preventive guidance on adherence and correct use of medications; and monitoring of comorbidities. The aim of this study was to draw the profile of pharmaceutical services in a community pharmacy of Natal / RN for the population. Data collection was performed through the availability of reports by the company under study, totaling 606 calls from January to September 2019. Among the services offered, the pharmaceutical guidance (561) was the one with the highest demand for care, followed by measurement. blood pressure (336) and capillary blood glucose (207). We can correlate the search for these services with the reported pathologies, since 149 patients had hypertension and 124, diabetes. Therefore, making pharmaceutical services available to the population reaffirms the need to have patient health and well-being as a priority in any health service. The pharmacist has a unique role in the process of health care of the population, through guidance on the needs of appropriate pharmacological therapy and healthy attitudes to improve quality of life.